A Robust Mammary Organoid System to Model Lactation and Involution-like Processes - Charifou, Elsa; Sumbal, Jakub; Koledova, Zuzana; Li, Han; Chiche, Aurélie (Bio-protocol, 2021)
The mammary gland is a highly dynamic tissue that changes throughout reproductive life, including growth during puberty and repetitive cycles of pregnancy and involution. Mammary gland tumors represent the most common cancer diagnosed in women worldwide. Studying the regulatory mechanisms of mammary gland development is essential for understanding how dysregulation can lead to breast cancer initiation and progression. Three-dimensional (3D) mammary organoids offer many exciting possibilities for the study of tissue development and breast cancer. In the present protocol derived from Sumbal et al., we describe a straightforward 3D organoid system for the study of lactation and involution ex vivo. We use primary and passaged mouse mammary organoids stimulated with fibroblast growth factor 2 (FGF2) and prolactin to model the three cycles of mouse mammary gland lactation and involution processes. This 3D organoid model represents a valuable tool to study late postnatal mammary gland development and breast cancer, in particular postpartum-associated breast cancer. Graphic abstract: Mammary gland organoid isolation and culture procedures.
Keywords: Involution; Lactation; 3D organoid; Mouse; Ex vivo; Mammary gland